Sensitivity of magnetic properties to chemical pressure in lanthanide garnets Ln3A2X3O12, Ln = Gd, Tb, Dy, Ho, A = Ga, Sc, In, Te, X = Ga, Al, Li. (1st September 2017) - Mukherjee, P; Sackville Hamilton, A C; Glass, H F J; Dutton, S E
Abstract: A systematic study of the structural and magnetic properties of three-dimensionally frustrated lanthanide garnets Ln 3 A 2 X 3 O12, Ln   =  Gd, Tb, Dy, Ho, A   =  Ga, Sc, In, Te, X   =  Ga, Al, Li is presented. Garnets with Ln   =  Gd show magnetic behaviour consistent with isotropic Gd 3+ spins; no magnetic ordering is observed for T   ⩾  0.4 K. Magnetic ordering features are seen for garnets with Ln   =  Tb, Dy, Ho in the temperature range 0.4  <   T   <  2.5 K, however the nature of the magnetic ordering varies for the different Ln as well as for different combinations of A and X . The magnetic behaviour can be explained by tuning of the magnetic interactions and changes in the single-ion anisotropy. The change in magnetic entropy is evaluated from isothermal magnetisation measurements to characterise the magnetocaloric effect in these materials. Among the Gd garnets, the maximum change in magnetic entropy per mole (15.45 J K −1 m o l G d − 1 ) is observed for Gd3 Sc2 Ga3 O12 at 2 K, in a field of 9 T. The performance of Dy3 Ga5 O12 as a magnetocaloric material surpasses the other garnets with Ln   =  Tb, Dy, Ho.